Effect of Passive Pile on 3D Ground Deformation and on Active Pile Response - Bingxiang Yuan; Rui Chen; Jun Teng; Tao Peng; Zhongwen Feng (The Scientific World Journal)
Using a series of model tests, this study investigated the effect of a passive pile on 3D ground deformation around a laterally loaded pile and on that laterally loaded pile’s response in sand. The active pile head was subjected to lateral loads, and the passive pile was arranged in front of the active pile. In the model tests, the distance between the two pile centers was set to zero (i.e., a single pile test), 2.5, 4, and 6 times the pile width (B). The 3D ground surface deformations around the active and passive piles were obtained using a newly developed Stereo-PIV technique. The experimental results showed that the ground surface movements were restrained by the passive pile when the pile spacing was less than 6B. The response of the active pile was affected by the passive pile when the pile spacing was less than 4B. This study combined the response of the active pile and surrounding 3D ground deformation to investigate the effect of the passive pile, which is useful to further understand the pile-soil-pile interactions and to enhance pile foundation design in engineering practice.